Exploring the effective parameters on the photocatalytic activity of TiO2 nanoparticles - Sa'aya, Nurul Syahirah Nasuha; Abdul Halim, Norhana; Tajuddin, Hairul Anuar; Norrrahim, Mohd Nor Faiz; Ngah Demon, Siti Zulaikha; Che Ros, Fadhlina; Aziz, Shujahadeen; Hamsan, Muhammad Hafiz; Mohd Azmi, Ahmad Farid; Zainol Abidin, Nadiah Husseini (Elsevier B.V., 2025)
The growing challenge of environmental pollution has driven intense research into advanced materials for pollutant degradation. Among them, titanium dioxide (TiO2) nanoparticles stand out for their efficiency in the photocatalytic degradation of organic pollutants, offering a promising solution for environmental remediation. In this study, TiO2 nanoparticles were synthesized and characterized to measure their structural, morphological, and optical properties, which directly influence their photocatalytic degradation of methylene blue (MB), a model organic dye. TiO2 nanoparticles were synthesized via the sol-gel method, enabling fine-tuned control over their crystallization and purity, and subsequently characterized using UV–Vis spectroscopy, field emission scanning electron microscopy (FESEM), Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and a particle size analyzer. The photocatalytic activity was evaluated by measuring the degradation rate of MB under UV light irradiation. One hour of sonication was employed after the optimization study to enhance the dispersion of the nanoparticles, resulting in a more uniform size and shape for further characterization. Raman spectroscopy confirmed the presence of both anatase and rutile phases, with peaks at 386 cm−1 and 516 cm−1 indicating anatase, while the rutile phase was identified by peaks at 451 cm−1 and 615 cm−1. Fourier Transform Infrared (FTIR) spectroscopy confirmed characteristic bond formations at 1643 cm−1 (Ti-OH) and 3338 cm−1(O–H). The degradation analysis was performed via UV–Vis spectrophotometer, which demonstrated a decrease in absorbance at λmax of 662 nm within 240 min. Additionally, UV–Vis spectroscopy was employed to determine the band gap energy of TiO2, calculated to be approximately 3.19 eV. Morphological analysis using FESEM revealed flake-like structures with an average size distribution of 52 nm, consistent with the nanoscale distribution observed using the particle analyzer and UV–Vis spectroscopy. In summary, this study successfully synthesized TiO2 nanoparticles with a mixed crystalline phase, achieving about 96.6 % photocatalytic efficiency for MB degradation, highlighting their potential for environmental treatment applications.